Fads and Facts about Vitamin D - Zawada, Edward T. Jr (IntechOpen, 2019)
Vitamin D is the subject of great controversy in the medical field. Uncertainties surround its use, including how much to give, what forms to use, and so on. This book attempts to clear up the confusion by providing concise and comprehensive information on vitamin D. Chapters cover such topics as the earliest investigations of vitamin D, subsequent studies of extraskeletal consequences of vitamin D deficiency, and clinical application of correction of vitamin D.